Lubiprostone for constipation and irritable bowel syndrome with constipation. (December 2008) - Tuteja, Ashok K; Rao, Satish SC
Chronic constipation and irritable bowel syndrome are heterogeneous disorders characterized by altered bowel habits, abdominal discomfort and/or difficult defecation. These conditions have a significant impact on patients' quality of life, as well as on the US economy, both in terms of healthcare costs and lost productivity. Treatment typically begins with lifestyle changes, increased fiber intake and osmotic and stimulant laxative intake. However, treatments for constipation vary in terms of their efficacy and safety. Furthermore, surveys of physicians and patients have revealed a strong desire for improved therapeutic options. Lubiprostone is a synthetic bicyclic fatty acid that is gut selective and stimulates type 2 chloride channels, resulting in increased chloride, sodium and water secretion into the lumen. The increased fluid secretion causes luminal distension, secondary peristalsis and laxation. Randomized Phase III trials have shown that lubiprostone is efficacious in the treatment of chronic idiopathic constipation and irritable bowel syndrome with constipation. The US FDA has approved lubiprostone at a dose of 24 µg twice daily for the treatment of chronic idiopathic constipation in adults, and at a dose of 8 µg twice daily for irritable bowel syndrome with constipation in adult women. Nausea, diarrhea and headaches are the most commonly reported side effects. In long-term studies, lubiprostone appears to be safe.